PERLINDUNGAN HAK JAMINAN SOSIAL BAGI PEKERJA MIGRAN INDONESIA DI MALAYSIA DITINJAU DARI PERSPEKTIF HUKUM INTERNASIONAL - Zhein Fajar Rheina; Sutiarnoto; Istislam Istislam; Agusmidah (Sabtida, 2024)
Abstract: Working abroad or what is called Migration is a step taken by workers in Indonesia to improve the quality of life, so as to obtain a decent life. The current PMI number has positive and negative values. Problems regarding PMI will continue to arise if PMI abroad are not given any protection. This Normative Research discussesProtection of Indonesian Migrant Workers as an indicator of fulfilling human rights according to International Law, The role of the ILO in implementing Employment Standards related to Social Security Protection for Migrant Workers, Social Security Program Policy for PMI in Malaysia. The method used in writing this thesis is Normative Juridical research, namely research using secondary data which is primary, secondary and tertiary legal materials through international agreements, legal regulations, legal books and the internet. The data analysis used is a qualitative data analysis method. Based on this, the author can conclude that International Law provides protection for social security rights as an indicator of fulfilling human rights for every migrant worker by ratifying the UDHR which specifically addresses human rights issues. In the international scope, protection is also provided through international organizations that collaborate with various multilateral institutions to establish employment standards for workers. Indonesia has a policy to provide protection for PMI in the form of Law no. 18 of 2017 concerning the Protection of Indonesian Migrant Workers which contains provisions that placement and protection are integrated within the authority of the Ministry of Manpower as well as providing more in-depth guidance and advocacy regarding the Agreement between workers and employers in order to increase legal awareness and better legal protection for prospective PMI’s.